Perception of Immigration among University Students (A Comparative Analysis Istanbul-Şırnak Example) - Bayram, Kayhan; Şengül, Fatma Nur (My University, 2023)
The subject of our study is the attitude of university students towards immigrants, especially Syrian immigrants, who migrated to Türkiye for various reasons. A survey technique was used to explain these attitudes. Some demographic questions about attitudes towards immigrants and the “Immigrant (Syrian) Perception Scale” were included in the survey. The study population consists of university students, and the sample group consists of university students studying in Şırnak and Istanbul. A total of 302 university students, 151 from Istanbul and 151 from Şırnak, participated in the study, using snowball and purposive sampling methods. As a result of the study, it was seen that the attitude of university students towards immigrants was negative, they found immigrants disturbing in terms of economy and security, and it was determined that university students were disturbed by the presence of immigrants. It has been determined that university students residing in Istanbul have a more negative attitude towards Syrian immigrants than those residing in Şırnak. In addition, it has been determined that as the education level, age, and religiosity increase, the attitude towards immigrants becomes more positive; but it does not differ according to gender, or economic level.
Keywords: Migration; Syrian Immigrants; University Students.; Immigrant Perception